2014
DOI: 10.2146/ajhp140073
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Medical Subject Headings thesaurus for pharmacy

Abstract: Imbalances and gaps were found in MeSH coverage of pharmacy concepts and terminology relative to MeSH terminology specific to the nursing and dentistry professions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Of note, is that the pharmacy-specific MeSH terms less frequently used (under 5%) were used to index a total of 1201 articles, whereas a previous research showed that over 2000 pharmacy articles, on average, would be indexed under the 17 proposed pharmacy-specific MeSH terms. 9 Another example of a potential inappropriateness in MeSH assignment in the pharmacy field is that about 12% (n ¼ 107) of the articles published in the Am J Pharm Educ, whose purpose is "to document and advance pharmaceutical education in the United States and internationally" (as defined by the journal's editorial board), were not indexed with any of the education specific MeSH terms: 'Education, Pharmacy,' 'Education, Pharmacy, Continuing,' or 'Education, Pharmacy, Graduate.' A similar study on the field of Pharmacoepidemiology/Drug Utilization analyzed the indexation of published articles under the MeSH terms "Pharmacoepidemiology," Table 5 Prevalence of pharmacy-specific MeSH terms used to index articles in each of the pharmacy journals analyzed "Drug Utilization" and "Drug Utilization Review."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of note, is that the pharmacy-specific MeSH terms less frequently used (under 5%) were used to index a total of 1201 articles, whereas a previous research showed that over 2000 pharmacy articles, on average, would be indexed under the 17 proposed pharmacy-specific MeSH terms. 9 Another example of a potential inappropriateness in MeSH assignment in the pharmacy field is that about 12% (n ¼ 107) of the articles published in the Am J Pharm Educ, whose purpose is "to document and advance pharmaceutical education in the United States and internationally" (as defined by the journal's editorial board), were not indexed with any of the education specific MeSH terms: 'Education, Pharmacy,' 'Education, Pharmacy, Continuing,' or 'Education, Pharmacy, Graduate.' A similar study on the field of Pharmacoepidemiology/Drug Utilization analyzed the indexation of published articles under the MeSH terms "Pharmacoepidemiology," Table 5 Prevalence of pharmacy-specific MeSH terms used to index articles in each of the pharmacy journals analyzed "Drug Utilization" and "Drug Utilization Review."…”
Section: Discussionmentioning
confidence: 99%
“…6 PubMed uses the NLM's controlled vocabulary thesaurus -the Medical Subject Headings (MeSH) -for indexing and cataloging articles. 7,8 Although criticized for not appropriately covering some areas, such as pharmacy, 9 the MeSH database is continuously updated and revised annually. 7 The intent of using the MeSH terminology is to facilitate search retrieval by eliminating (or accounting for) the use of variant terminology for the same concept.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This knowledge representation is a list of codes that can be used to classify appraisals. Other coding schemes or controlled vocabularies, such as Medical Subject Headings (MeSH), facilitate information retrieval and contextualization (Minguet et al , 2014). Similarly, this knowledge representation for appraisal concepts seek to improve data management by enabling structured annotation and large-scale reasoning, which in the long-term will impart actionable knowledge for clinical, scientific, policy decision-making, and for meta-research.…”
Section: Introductionmentioning
confidence: 99%